Should we screen patients with venous thromboembolism for previously undiagnosed malignancy? A systematic review and pilot trial - Carrier, Marc (University of Ottawa (Canada), 2008)
Statement of the problem. Malignancy screening for patients with venous thromboembolism (VTE) is controversial. Methods of investigation. A systematic review was performed to quantify the additional value of an extensive malignancy screening strategy compared to a more limited screen. A pilot study assessing the utility of a comprehensive computed tomography as a malignancy screening tool was performed. Results. The systematic review demonstrated that an extensive malignancy screening strategy increases the proportion of previously undiagnosed malignancy detected from 49.5% (95% CI: 40.5-58.5) (limited screening alone) to 67.4% (95% CI: 59.0-75.6) (limited screen + CT). The pilot study showed that approximately 6 eligible consenting patients can be recruited per month. Conclusion. Previously undiagnosed malignancies are common in patients with unprovoked VTE. These malignancies are more likely to be detected by an extensive screening strategy (limited screen and CT). A clinical trial in that particular clinical setting is feasible.
Keywords: Health Sciences, Public Health.; Health Sciences, Epidemiology.